DO YOU KNOW THE WORD? SEBUAH STUDI TENTANG LEVEL KOSAKATA PADA MAHASISWA BARU: Do you know the word? A Study on vocabulary level of freshman) - Boni Saputra (UIR Press, 2020)
Vocabulary is part of language teaching and learning. Sufficient words usage ease students cope with academic assignments. This study tries to find out vocabulary level of freshman at English department State Polytechnic of Bengkalis. The method of the research is descriptive. Instruments used in gathered the data is set of vocabulary level test designed by Nation (1983) and developed by Schmitt, N., D. Schmitt, and C. Clapham. 2001. The population of the study is 16 freshman of Diploma program. The result of the test showed that most of the students are below 1000 vocabulary level. The finding revealed that the learners have limited vocabulary. It also brings two implications to the teaching. First, Lecturers should provide ekstra vocabulary training in lessons. Then, instruction language used should be adjusted between target language and mother tongue.